Post heat treatment microbial contaminants and quantitative risk analysis of s. Aureus in sliced vacuum packed french polony - Moyo, Bonang B. (Midlands State University, 2017)
Contamination of luncheon meats by bacteria has resulted in premature product spoilage and food poisoning outbreaks as well as major product recalls. A quantitative microbial assessment of air, surfaces, equipment and personnel hands (swabs), and finished product was conducted on 3 batches during separate visits at various processing stages during production of sliced vacuum packed French polony at a large meat processing plant in Zimbabwe. The aim was to determine the routes of microbial cross contamination onto French polony during slicing and packing as well as the subsequent food safety threat posed to consumers. The post-cooking environment had relatively high levels of S. aureus, yeast and molds while equipment and surfaces proved to be unhygienic as indicated by high counts of TBC and coliforms. S. aureus was the only pathogen detected in the finished product (2.04log CFU/g) and personnel hands and the counts exceeded acceptable international standards. A Quantitative Risk Assessment Model process that described steps and behaviour of S. aureus along the sliced vacuum packed French polony chain was created and the exposure of S. aureus per serving was high (> 6log CFU/serving) in over 65% of each serving and consequently the probability of illness too. Overall, there is a relatively high level of risk of microbial contamination of French polony during slicing and packing from different sources at the meat processing plant investigated and it is paramount to consolidate the quality assurance programs so as to ensure the safety of consumers of products produced at this plant.